Improvement of functionality after chitosan-modified zein biocomposites. Issue 3 (11th February 2017) - Yu, Hao; Li, Wei; Liu, Xing; Li, Chen; Ni, Hong; Wang, Xiong; Huselstein, Céline; Chen, Yun
Abstract: A series of chitosan-modified zein composite films were fabricated from zein and chitosan by a process involving blending, solution casting and evaporation. Effects of chitosan content on the structure and physical properties of the composite films were investigated by Fourier transform infrared spectroscopy, differential scanning calorimetry, scanning electron microscopy, tensile testing, water absorption measurement and water contact angle measurement. The results showed that the zein/chitosan composite films were fabricated successfully due to the formation of hydrogen bonds between zein and chitosan, and the thermal stability, water absorption, hydrophilicity, tensile strength, flexibility of the composite films increased with an increase in chitosan content from 0 to 50%. The cytotoxicity and cytocompatibility of the composite films were evaluated by 3-[45-dimethyl-2-thiazoly1]-25-diphenyl-2H-tetrazolium bromide (MTT) assay and in vitro cell culture, which showed that the films have non- or low-cytotoxicity, and chitosan promoted the growth, adhesion and proliferation of the cells. These results indicated that chitosan-modified zein composite films might have potentials applications as biomaterials.